Wisdom and Law in the Hebrew Bible and at Qumran - Hempel, Charlotte (Journal for the study of Judaism, 2017)
This article begins by noting the paucity of engagement between scholarship on the Dead Sea Scrolls (dss) and a number of significant studies on the relationship of wisdom and law in the Hebrew Bible. A substantial case study on Proverbs 1-9 and the Community Rule from Qumran is put in conversation with the seminal work of, especially, Moshe Weinfeld on Deuteronomy and its refinement by subsequent research to trace a dynamic interaction between wisdom and law in the Second Temple period. The article ends with critical reflections on the wide-spread model of segmenting ancient Jewish literature and those responsible for it into neat categories such as wisdom and law. It is argued that such a model presupposes a degree of specialization that is not borne out by the range of literature that found its way into the Hebrew Bible or the caves in the vicinity of Khirbet Qumran.